Tendon Tissue Engineering: Effects of Mechanical and Biochemical Stimulation on Stem Cell Alignment on Cell‐Laden Hydrogel Yarns. Issue 7 (6th February 2019) - Rinoldi, Chiara; Costantini, Marco; Kijeńska‐Gawrońska, Ewa; Testa, Stefano; Fornetti, Ersilia; Heljak, Marcin; Ćwiklińska, Monika; Buda, Robert; Baldi, Jacopo; Cannata, Stefano; Guzowski, Jan; Gargioli, Cesare; et al.
Abstract: Fiber‐based approaches hold great promise for tendon tissue engineering enabling the possibility of manufacturing aligned hydrogel filaments that can guide collagen fiber orientation, thereby providing a biomimetic micro‐environment for cell attachment, orientation, migration, and proliferation. In this study, a 3D system composed of cell‐laden, highly aligned hydrogel yarns is designed and obtained via wet spinning in order to reproduce the morphology and structure of tendon fascicles. A bioink composed of alginate and gelatin methacryloyl (GelMA) is optimized for spinning and loaded with human bone morrow mesenchymal stem cells (hBM‐MSCs). The produced scaffolds are subjected to mechanical stretching to recapitulate the strains occurring in native tendon tissue. Stem cell differentiation is promoted by addition of bone morphogenetic protein 12 (BMP‐12) in the culture medium. The aligned orientation of the fibers combined with mechanical stimulation results in highly preferential longitudinal cell orientation and demonstrates enhanced collagen type I and III expression. Additionally, the combination of biochemical and mechanical stimulations promotes the expression of specific tenogenic markers, signatures of efficient cell differentiation towards tendon. The obtained results suggest that the proposed 3D cell‐laden aligned system can be used for engineering of scaffolds for tendon regeneration. Abstract : Highly aligned hydrogel yarns are fabricated using a novel system employing a wet‐spinning technique to recapitulate the structure and morphology of tendon tissue. Scaffolds are loaded with human bone‐marrow‐derived stem cells and subjected to mechanical stretching and biochemical stimulation. The combined effect of these stimuli results in cell preferential orientation, tenogenic differentiation, and collagen expression.